GENERAL PRINCIPLES OF COST ACCOUNTING. - Prickett, A. L. (The Accounting Review, 1944)
Cost accounting as such is of comparatively recent origin. Cost concepts are intermingled with expense in general, with value concepts, with economic theory, with legal decisions and statutory expression and with war emergency directives to the extent that basic cost accounting, if such there be, becomes increasingly difficult to untangle from the confused, related, but not identical strands. Costs chargeable to purchases of materials should include invoice costs plus incoming transportation, insurance, customs taxes and duties, and similar direct charges, in so far as they can be identified with the material. If they cannot be so directly identified, there is no point to forced artificial identification and they should be listed with other unidentifiable costs as part of the overhead. Returns and allowances and trade discounts are proper deductions about which there is not so much controversy. Purchases discounts should be deducted in entirety, or on all amounts above a reasonable percentage for prompt payment, say one per cent, or not deducted at all.